What we have learnt from the SARS epdemics in mainland China? - Cao, Wuchun (Glob Health J, 2019)
This article provides an overview of the severe acute respiratory syndrome (SARS) epidemics in mainland China and of what we have learned since the outbreak. The epidemics spanned a large geographical extent but clustered in two regions: first in Guangdong Province, and about 3 months later in Beijing and its surrounding areas. The resulting case fatality ratio of 6.4% was less than half of that in other SARS-affected countries and regions, partly due to younger-aged patients and a higher proportion of community-acquired infections. Strong political commitment and a centrally coordinated response were most important for controlling SARS. The long-term economic consequence of the epidemic was limited. Many recovered patients suffered from avascular osteonecrosis, as a consequence of corticosteroid usage during their infection. The SARS epidemic provided valuable experience and lessons relevant in controlling outbreaks of emerging infectious diseases, and has led to fundamental reforms of the Chinese health system. Additionally, the epidemic has substantially improved infrastructures, surveillance systems, and capacity to response to health emergencies. In particular, a comprehensive nationwide internet-based disease reporting system was established.